Performance and stability of historic casein formaldehyde - Kaner, Jake; Loras, Florin; Ratnasingam, Jegatheswaran (Plastics Heritage European Association, 2017)
Casein formaldehyde was manufactured between 1904 and 1982 in Western Europe both by International Galalith Gesellschaft (IGG) and Erinoid Ltd. (amongst others). Charles Rennie Mackintosh used it in his designs for furniture commissioned by Wenman Joseph Bassett-Lowke. Casein formaldehyde may be identified through a range of simple and analytical methods available to most conservators in private and public practice. We can control the loss of colour and protect the surface finish by minimising light exposure. Material, aged and distorted, may be reversed if the correct conservation procedures are observed and implemented.